Type II supernovae as probes of environment metallicity: observations of host He II regions - Anderson, J. P. (2016)
Context. Spectral modelling of type II supernova atmospheres indicates a clear dependence of metal line strengths on progenitor metallicity. This dependence motivates further work to evaluate the accuracy with which these supernovae can be used as environment metallicity indicators. Aims. To assess this accuracy we present a sample of type II supernova host H II-region spectroscopy, from which environment oxygen abundances have been derived. These environment abundances are compared to the observed strength of metal lines in supernova spectra. Methods. Combining our sample with measurements from the literature, we present oxygen abundances of 119 host H II regions by extracting emission line fluxes and using abundance diagnostics. These abundances are then compared to equivalent widths of Fe II 5018 Å at various time and colour epochs. Results. Our distribution of inferred type II supernova host H II-region abundances has a range of ∼0.6 dex. We confirm the dearth of type II supernovae exploding at metallicities lower than those found (on average) in the Large Magellanic Cloud. The equivalent width of Fe II 5018 Å at 50 days post-explosion shows a statistically significant correlation with host H II-region oxygen abundance. The strength of this correlation increases if one excludes abundance measurements derived far from supernova explosion sites. The correlation significance also increases if we only analyse a "gold" IIP sample, and if a colour epoch is used in place of time. In addition, no evidence is found of a correlation between progenitor metallicity and supernova light-curve or spectral properties - except for that stated above with respect to Fe II 5018 Å equivalent widths - suggesting progenitor metallicity is not a driving factor in producing the diversity that is observed in our sample. Conclusions. This study provides observational evidence of the usefulness of type II supernovae as metallicity indicators. We finish with a discussion of the methodology needed to use supernova spectra as independent metallicity diagnostics throughout the Universe.